Changing Patterns of Attendance at Religious Services in Canada, 1986-2008 - Eagle, David E. (Journal for the scientific study of religion, 2011)
According to the General Social Survey, the combined rate of weekly and monthly attendance at religious services in Canada has declined by about 20 points from 1986 to 2008. Approximately half of this decline stems from the increase in the proportion of people reporting no religion, who, for the most part, do not attend religious services. The other portion of this decline is attributable to eroding attendance rates among Catholics, particularly older Catholics, and Protestants in Québec. Attendance rates for Protestants outside of Québec show signs of increase. The reported increase in weekly attendance in Canada by the Project Canada surveys and cited by Bibby as a possible indicator of a religious renaissance is revealed as an artifact in the data due to an oversample of Protestants. I find another weighting problem in the Canadian Survey of Giving, Volunteering and Participating that leads to underestimates of aggregate religious attendance rates.